2018
DOI: 10.1159/000494092
|View full text |Cite
|
Sign up to set email alerts
|

Headache at the Time of First Symptom Manifestation of Multiple Sclerosis: A Prospective, Longitudinal Study

Abstract: Aims: Headaches have not been considered a typical symptom of multiple sclerosis (MS), although since 2000, almost every study showed high prevalence. We screened 50 MS patients at the time of first occurrence of neurological symptoms and found the highest prevalence of headache in MS that was ever recorded (78%). Postmortem histological analyses of MS patients’ brains revealed lymphoid follicle-like structures in the cerebral meninges and a pathophysiological link between headache, and high inflammatory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…Meningoencephalitis-like pathology with fever, severe headache, and pleocytosis in the cerebrospinal fluid (CSF) has been reported in both disease complexes, NMOSD and MOGAD (74,121), most likely due to meningeal inflammation (122,123).…”
Section: Encephalitis-associated Headachementioning
confidence: 99%
“…Meningoencephalitis-like pathology with fever, severe headache, and pleocytosis in the cerebrospinal fluid (CSF) has been reported in both disease complexes, NMOSD and MOGAD (74,121), most likely due to meningeal inflammation (122,123).…”
Section: Encephalitis-associated Headachementioning
confidence: 99%
“…After abstract screening and manual searching of references, we search out 62 articles meeting the criteria for full‐text reviewing. Among the 62 articles, 46 were excluded and 16 research articles were included in the final meta‐analysis (Beckmann & Türe, 2019; Busillo et al., 2014; D'Amico et al., 2004; Doi et al., 2009; Gebhardt, Kropp, Hoffmann, & Zettl, 2018; Gustavsen et al., 2016; Katsiari, Vikelis, Paraskevopoulou, Sfikakis, & Mitsikostas, 2011; Kister et al., 2010; Möhrke, Kropp, & Zettl, 2013; Nicoletti et al., 2008; Özer, Ergün, & İnan, 2018; Putzki et al., 2009; Sorgun, Yucesan, & Yasemin, 2013; Srivastava, Wang, Ugurlu, & Amezcua, 2016; Vacca et al., 2007; Villani et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“… Frequent headaches Headaches – a study found high prevalence of headaches in 78% of the MS patients studied. 27 Another study reported 16.3% of MS patients with migraine, 23.5% with tension headache, none with cluster headaches, and 60.2% of the MS patients with headache remained unclassified. 28 Rigidity of the tongue and inability to take food in easily Dysphagia – in a study, 31.7% of the MS patients were classified as having dysphagia.…”
Section: Discussionmentioning
confidence: 98%
“…Pain is a problem encountered in at least 50% of MS patients 26 , and headaches are common in 78% of the cases. 27 , 28 Another series of manifestations may be attributed to a dysfunction of the autonomic nervous system (ANS) such as “ cold inversion in the morning and evenings, spontaneous sweating, and feeling of Yin Qi shrouding the skin and hair ”, the latter explained as “ chills or a feeling of cold ”. 29 , 30 The “ difficulty voiding of bound stools ” was identified as constipation, common in 50% of the MS patients.…”
Section: Discussionmentioning
confidence: 99%